Marolo (Annona crassiflora): bioacessibilidade de compostos bioativos com potencial à longevidade humana - Todescato, Angélica Pereira (2022)
Marolo (Annona crassiflora) is a typical fruit from the Brazilian Cerrado, a source of different bioactive compounds. Recent studies have shown a direct relationship between polyamines, especially spermidine, and human longevity. This work aimed to determine the bioaccessibility of bioactive compounds in marolo pulp with potential for human longevity. The contents of total phenolic compounds, total flavonoids and antioxidant potential were determined by spectrophotometric methods. Ten bioactive amines were investigated by high performance liquid chromatography by reverse phase ion pairing, namely: putrescine, cadaverine, agmatine, spermidine, spermine, 2-phenylethylamine, serotonin, tryptamine, histamine and tyramine. Bioaccessibility was performed following the INFOGEST protocol. The marolo pulp showed 66.15 μmol ET/g for antioxidant potential (ABTS) and 65.94 μmol ET/g (DPPH), 9.16 mg EAG/g for total phenolics, 7.26 mg EC/g for flavonoids totals. The indices of antioxidant potential after in vitro digestion by the ABTS and DPPH methods were 35.3% and 47.6%, respectively. Bioaccessibility indexes were 21.8%, and 17.6% for total phenolics and flavonoids. Only putrescine, spermidine and tyramine were detected in marolo pulp, with contents of 20.65, 6.32 and 31.96 mg/kg and bioaccessibility index of 59.4%, 36.8% and 89.6%, respectively. This research contributes with unprecedented information about the bioaccessibility of bioactive compounds from marolo pulp, characterized by low bioaccessibility of phenolic compounds and total flavonoids; moderate levels of putrescine and spermidine and high levels of tyramine. The ABTS assay on the effect of digestion on antioxidant potential was the same for the gastric and intestinal phases; while for DPPH, the antioxidant content in the intestinal phase was higher than in the gastric phase. It is suggested that future research be carried out to evaluate the effect of different processing of marolo pulp on the bioaccessibility of bioactive compounds and on their antioxidant potential.